Identification of diverticular bleeding needs early colonoscopy rather than preparation - Mizuki, Akira; Tatemichi, Masayuki; Nakazawa, Atsushi; Tsukada, Nobuhiro; Nagata, Hiroshi; Kanai, Takanori (Endoscopy International Open, 2022)
Background and study aims When patients present with acute colonic diverticulum bleeding (CDB), a colonoscopy is performed to identify stigmata of recent hemorrhage (SRH), but valuable time can be lost in bowel preparation. This study retrospectively examined groups of patients who either had a standard pre-colonoscopy regimen or no preparation.Patients and methods This study compared data from 433 patients who either followed a lengthy regimen of bowel preparation (prepared group, 266 patients) or had no preparation (unprepared group, 60 patients). We compared the association between time (hours) between admission before starting a colonoscopy (TMS) and identification of SRH using a chi-square test.Results In 48 of 60 cases (80.0 %) in the unprepared group, a total colonoscopy was performed and the time to identify SRH was decreased. The respective rates of SRH identification in the unprepared and prepared groups were 55.2 % (16/29) vs. 46.7 % (7/15) if the TMS was < 3 hours; 47.1 % (8/7) vs. 36.8 % (35/95) in 3 to 12 hours; 0 % (0/3) vs. 22.0% (13/59) in 12 to 18 hours; and 21.8 % (3/11) vs. 20.6% (42/204) in > 18 hours. There were no significant differences between the two groups. However, the SRH identification rates before and after 12 hours were 42.3 % (66/156) and 20.9 % (58/277) (P < 0.001).Conclusions Our data suggest that the bowel preparation method before colonoscopy is an independent variable predicting success in identifying SRH among patients with CDB. Decreasing the time before colonoscopy to no more than 12 hours after admission played an important role in identifying SRH.